1996
DOI: 10.1007/978-1-4899-3434-5
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia — A Social Approach

Abstract: Apart from any fair dealing for the purposes of research or private study, or criticism or review, as permitted under the UK Copyright Designs and Patents Act, 1988, this publication may not be reproduced, stored, or transmitted, in any form or by any means, without the prior permission in writing of the publishers, or in the case of reprographic reproduction only in accordance with the terms of the licences issued by the Copyright Licensing Agency in the UK, or in accordance with the terms of licences issued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Branfield & Maynard Campbell, c. 2000) and a need for increased official and public understanding of stroke in younger people (e.g. Jordan & Kaiser 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branfield & Maynard Campbell, c. 2000) and a need for increased official and public understanding of stroke in younger people (e.g. Jordan & Kaiser 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Factors people with aphasia say influence their return to work include availability of alternative jobs, working patterns and conditions, attitudes of employers and family members, and availability of education/training (Rolland & Berlin, 1993;Jordan & Kaiser, 1996;Parr et al, 1997;Garcia et al, 2000). One focus group study has shown that such factors may interact with the person's impairments to create barriers to employment (Garcia et al, 2000).…”
mentioning
confidence: 99%
“…In addition, data from interviews with aphasic individuals have been used to prompt and illustrate reflection on the impact of aphasia [Lafond et al, 1993] and the relevance of alternative models of disability [Jordan and Kaiser, 1996]. Many of these studies and accounts draw on the personal experience of individuals or of small groups of aphasic people.…”
Section: Qualitative Research: Some Useful Distinctionsmentioning
confidence: 99%
“…Usually reading and writing are more impaired than oral communication. 19 The commonly recognised types of aphasia include:…”
Section: Aphasiamentioning
confidence: 99%
“…Sometimes the impairment can be so subtle that it only manifests itself when the patient is put into unfamiliar or stressful surroundings and the language consists of 'low frequency' words that (s)he would be unlikely to come across in everyday life. 19 Aphasia affects each person differ ently and their communication diffi cul ties can also change from day to day or even hour to hour. They are likely to be worse when tired or under pressure, 21 and guidance from several aphasia asso ciations recommend a number of strate gies for communicating more effectively with people with aphasia.…”
mentioning
confidence: 99%